(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Investigation of intestinal helminths in Clarias gariepinus from Jibia reservoir was carried out. Clarias gariepinus samples were purchased from fisher folks and identified at each of the three landing sites of the reservoir. Fish sampling was carried out between March to August, 2021. A total of 100 randomly selected samples of Clarias gariepinus obtained were examined. The fish samples were transported to Biology laboratory, Federal University Dutsin-Ma for standard morphometric determination and examination of the gut for parasites. The endo-parasitic fauna isolated were examined. Data were analysed using descriptive statistics and chi-square. Only cestodes and nematodes were found in the gut. A total number of sixty nine (69) intestinal parasites; cestodes (Monibothrium larvae, Monibothrium sp.) and nematodes (Camallanus sp., Capillaria sp. and Contracaecum sp.) were isolated. The cestode Monibothrium larvae were the most minor intense (9 worms), followed by the nematodes Camallanus sp., Capillaria sp. and Contracaecum sp. which were moderately intense (15, 19 and 10 worms, respectively). However, only 16 cestode worms belonging to Monobothrium were collected from the stomach and intestine of the experimental species from the three sample locations. Heavy infestation with a broad number of parasites in fish hosts could reduce performance and productivity of the species, especially in the wild. It is therefore recommended that the gastro-intestinal tract of harvested Clarias gariepinus from the study area should be discarded rather than consumed to prevent the transmission of zoonotic diseases